Pengaruh Social Media Marketing terhadap Purchase Intention dengan Brand Image Sebagai Intervening (Studi pada Pengguna Wardah Kosmetik) - Asyahra, Anissa; Rivai, Alimuddin Rizal (Universitas Batanghari, 2024)
This exploration expects to test and decide the impact of virtual entertainment promoting on buy goals with brand picture as an interceding variable for clients and purchasers of Wardah items. The strategy utilized in this examination is a quantitative technique utilizing essential information got through a poll. The example for this exploration was 103 respondents utilizing a purposive inspecting procedure. The information was then investigated utilizing the SPSS variant 23 information handling application. The study found that social media marketing has a significant impact on brand image and has a positive influence. Web-based entertainment showcasing emphatically affects buy goals. Purchase intention is positively influenced by brand image. Online entertainment promoting is the most prevailing variable affecting buy aim. The model in this examination is noticeably flawed, thusly investigating different variables is fundamental.